Born abroad/contested at home: (schemes and transpositions of Bulgarian literary history in its inception phase) - Zlatanov, Blagovest (Literaturata, 2020)
Bulgarian Literary History as a conceptual framework as well as a disciplinary discourse is - not only in its previous formations but also in its present form - a product of very long and turbulent discussions in Slavic Studies conducted in the first three quarters of the 19th c. outside the ethnic and language borders of the subdued Bulgaria. Bulgarian intellectuals imported this extraneous conceptual model of Bulgarian literary history in Bulgaria soon after its liberation from Turkish rule in 1878. After a period of heated objections to the model the Bulgarian academic and public institutions adopted it as the only relevant prism for considering the Bulgarian literary past.